Comparison of ambulatory blood pressure monitoring and self-blood pressure monitoring for diagnosing white coat hypertension amongst pregnant women - Sood, Sandeep; Anne, Sirisha; Ashta, Kuldeep Kumar; Kumar, Ravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: White coat hypertension (WCH) is a common and well recognized phenomenon. It is also very prevalent amongst pregnant women and is often diagnosed as chronic/ gestational hypertension leading to unnecessary medications during pregnancy. ABPM is the gold standard for diagnosis of WCH. SBPM is an easy effective and reliable method to measure blood pressure but its efficacy needs to be tested and compared with ABPM in cases of WCH. It is important to compare the two methods in assessing WCH so SBPM can be utilized in cases of WCH, if found useful and efficacious. Methods: All pregnant women who presented to the ANC were screened for hypertension. Those who were diagnosed to be hypertensive in antenatal clinic and these patients were then admitted for ambulatory blood pressure monitoring (ABPM) for 24 hours and SBPM on 6 hourly bases for 5 days. Results: The ABPM and SBPB readings were noted, tabulated and compared. It was found that the prevalence of ‘WCH’ in this study using ABPM and SBPM were 47.368% (27/54) and 45.614% (26/54) respectively. Conclusions: The results in diagnosing WCH using ABPM and SBPM were comparable.